PERAN BAITUL MAAL WA TAMWIL (BMT) DALAM UPAYA PEMBERDAYAAN EKONOMI MASYARAKAT - Anam, Moh.; Mufida, Nur (Program Studi Ekonomi Syariah (ES) STAI Nahdlatul Ulama (STAINU) Malang, 2024)
This research aims to find out whether Baitul Maal wa Tamwil (BMT) has an active and important role in the non-bank financial sector. The presence of Baitul Maal wa-Tamwil (BMT) in an area is based on the fact that it has not been